Dual metal and Lewis base catalysis approach for asymmetric synthesis of dihydroquinolines and the α-arylation of aldehydes via N-acyliminium ions. Issue 87 (14th September 2015) - Volla, Chandra M. R.; Fava, Eleonora; Atodiresei, Iuliana; Rueping, Magnus
Abstract : A dual catalytic system consisting of indium triflate and a chiral imidazolidinone catalyzes the asymmetric addition of aldehydes to N -acyl quinoliniums furnishing optically active dihydroquinolines in good yields and excellent selectivities. Abstract : A dual catalytic system consisting of indium triflate and a chiral imidazolidinone catalyzes the asymmetric addition of aldehydes to N -acyl quinoliniums furnishing optically active dihydroquinolines in good yields and excellent selectivities. The products were further functionalized into optically active tetrahydroquinolines, quinolines and 6-oxa-2-aza-bicyclo[3.3.1]nonanes.